Metode Guru Dalam Mengatasi Kesulitan Membaca Permulaan Dikelas 1 SDN No 102105 Bandar Bejambu Kecamatan Tebing Tinggi - Aulia Febrianti Saragih; Salminawati Salminawati; Riris Nurkholidah Rambe (LPPM Politeknik Pratama, 2023)
The purpose of this study was to find out : (1) Students' ability to read beginning in class 1 SDN No 102105 Bandar Bejambu, Tebing Tinggi District, academic year 2020/2023, (2) Difficulties faced by students in starting reading in class 1 SDN No 102105 Bandar Bejambu Tebing Tinggi District and (3) how to overcome students' difficulties in reading beginning in grade 1 SDN No 102105 Bandar Bejambu, Tebing Tinggi District. The methology in this study uses qualitative research with descriptive methods. Respondents in this study were teachers, students and parents of students. Data collection techniques used are observation, interview and documentation methods. Data analysis used is data reduction, data presentation, and drawing conclusions. Furthermore, the technique of checking the validity of the data uses credibility, transferability, dependability and confirmability. The results of this study indicate that the ability of students in grade 1 has begun to increase from 20 students. There are 4 students who have difficulty reading, such as : 1) Some students are still confused about letters such as p-b, b-d, q-p, 2) have difficulty reading solid letters such as kh , ng, ny, sy, 3) students have not been able to spell, 4) inhibiting factors for students are internal and external students. Some of the teacher's ways to overcome early reading difficulties in grade 1 are to provide support such as reading habituation, paying attention to and motivating students, providing additional hours and free time and the teacher must also provide an approach, choose an effective beginning reading method for students, guide and create comfortable atmosphere, communicating with parents of students.